Impact of trazodone once-a-day on quality of life and functional recovery in adults with major depressive disorder: A prospective, observational study - Tellone, Valeria; Markovic, Oto; Strashimirova, Milena; Sani, Gabriele; Lenderking, William R; Margolis, Mary Kay; Fallone, Raffaella; Quarchioni, Elisa; Cattaneo, Agnese; Comandini, Alessandro (Brain and behavior, 2024)
BACKGROUND: Health-related quality of life (HRQL) is an important goal for patients with major depressive disorder (MDD), but whether antidepressants improve HRQL in these patients is unclear. Here, we describe the real-world effects of trazodone once-a-day (TzOAD) and selective serotonin reuptake inhibitor (SSRI) treatments on HRQL and functioning in adults with MDD. METHODS: This 8-week prospective, observational, open-label, multicenter study was conducted in adults with moderate or severe MDD for whom TzOAD or SSRI were prescribed as monotherapy. The primary outcome was life enjoyment and satisfaction assessed via the patient-reported Quality-of-Life Enjoyment and Satisfaction Questionnaire Short Form (Q-LES-Q-SF) from baseline to week 8. Secondary outcomes included change in Q-LES-Q-SF from baseline to weeks 1 and 2; severity of depressive symptoms using the Montgomery Åsberg Depression Rating Scale (MADRS) and sleep disturbance via the PROMIS SF-SD 8b questionnaire at weeks 1, 2, and 8; and overall functioning via the Sheehan Disability Scale (SDS), hedonic capacity using the Snaith-Hamilton Pleasure Scale (SHAPS), and cognitive dysfunction using the Perceived Deficits Questionnaire (PDQ-5) at baseline and week 8. RESULTS: The study included 208 adults with MDD (mean [SD] age = 50.2 [14.3] years; 68.6% female; 98.4% White). Life enjoyment and satisfaction improved from baseline to week 8 for both treatment groups: Q-LES-Q-SF mean (SD) scores were 27.5 (20.4) for the SSRI group and 39.0 (22.1) for the TzOAD group. Depressive symptoms and sleep disturbances also reduced from baseline to week 8: MADRS (SSRI, -15.7 [8.3]; TzOAD, -21.0 [9.8]); PROMIS SF-SD 8b (SSRI, -9.9 [12.6]; TzOAD, -22.0 [12.6]). Mean change scores in Q-LES-Q-SF, MADRS, and PROMIS SF-SD 8b improved as early as week 1 in both groups. Mean scores also improved from baseline to week 8 on SDS (SSRI, -9.2 [7.4]; TzOAD, -14.3 [7.5]), SHAPS (SSRI, -6.6 [4.3]; TzOAD, -8.3 [4.4]), and PDQ-5 (SSRI, -5.8 [4.5]; TzOAD, -7.7 [5.0]). CONCLUSIONS: In adults with MDD who received TzOAD or SSRIs, overall and individual HQRL domains improved rapidly and in parallel with improvements in depressive symptoms, with a slightly greater improvement observed in the TzOAD group.
Keywords: dospělí; Depressive Disorder, Major; trazodon; Female; Selective Serotonin Reuptake Inhibitors; Adult; výsledek terapie; ženské pohlaví; selective serotonin reuptake inhibitors; health‐related quality of life (HRQL); kvalita života; lidé; depresivní porucha unipolární; Recovery of Function; Treatment Outcome; Trazodone; trazodone; obnova funkce; Middle Aged; antidepresiva druhé generace; selektivní inhibitory zpětného vychytávání serotoninu; prospektivní studie; Male; Prospective Studies; Antidepressive Agents, Second-Generation; major depressive disorder; lidé středního věku; mužské pohlaví; Quality of Life; Humans